Unanswered Questions in Colombia’s Foreign Language Education Policy - Camilo Andrés Bonilla Carvajal; Isabel Tejada-Sánchez (Profile Issues in Teachers' Professional Development, 2016)
Following the trend of much of the Western, non-English speaking world, Colombia has tirelessly strived for spreading English education in an effort to augment economic benefits. This paper aims at providing a critical account of foreign language education policy in Colombia, with special attention to English. It outlines the impact of its multiple transitions over the past decades through a historical description that overviews all previous policies, the critical reception by scholars, and present-day initiatives. We then move on to analysing the choice of English as a synonym for bilingualism and conclude with emerging questions that are to be considered for future debates and reassessments of Colombia’s English-Spanish bilingual education policy.